2017
DOI: 10.1073/pnas.1710566114
|View full text |Cite
|
Sign up to set email alerts
|

Schwann cells use TAM receptor-mediated phagocytosis in addition to autophagy to clear myelin in a mouse model of nerve injury

Abstract: Ineffective myelin debris clearance is a major factor contributing to the poor regenerative ability of the central nervous system. In stark contrast, rapid clearance of myelin debris from the injured peripheral nervous system (PNS) is one of the keys to this system's remarkable regenerative capacity, but the molecular mechanisms driving PNS myelin clearance are incompletely understood. We set out to discover new pathways of PNS myelin clearance to identify novel strategies for activating myelin clearance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(180 citation statements)
references
References 41 publications
7
160
0
Order By: Relevance
“…Soon after injury, Schwann cells downregulate a myelin gene network and activate autophagy and phagocytic programs to carry out myelin clearance, which is further facilitated by recruited macrophages (Brosius Lutz et al 2017; Gomez-Sanchez et al 2015; Hirata and Kawabuchi 2002). Quantitation of myelin debris at 14 d post-injury did not reveal a significant difference in Eed cKO nerves compared to control nerves (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soon after injury, Schwann cells downregulate a myelin gene network and activate autophagy and phagocytic programs to carry out myelin clearance, which is further facilitated by recruited macrophages (Brosius Lutz et al 2017; Gomez-Sanchez et al 2015; Hirata and Kawabuchi 2002). Quantitation of myelin debris at 14 d post-injury did not reveal a significant difference in Eed cKO nerves compared to control nerves (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Soon after injury, repair cells derived from both myelinating and non-myelinating (Remak) Schwann cells create a structural and trophic environment that stimulates axon regeneration (Brosius Lutz and Barres 2014; Gomez-Sanchez et al 2017; Jessen and Mirsky 2016). Repair Schwann cells activate autophagy and phagocytosis mechanisms to remove myelin debris, which inhibit axon regrowth and branching (Brosius Lutz et al 2017; Gomez-Sanchez et al 2015; Mukhopadhyay et al 1994; Shen et al 1998), and promote recruitment of macrophages that further facilitate myelin removal and regeneration (Cattin et al 2015; Fischer et al 2008; Niemi et al 2013). Elongated Schwann cells distal to the injury site form Bands of Bungner, which serve as tracks for axonal regeneration (Arthur-Farraj et al 2012; Gomez-Sanchez et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While "breakdown" and "disintegration" of the myelin sheath has been used to describe the initial destruction of the bulky structure of compact myelin (Blümcke & Niedorf, 1966;Johnson et al, 1950;O'Daly & Imaeda, 1967), myelin "digestion" has also been used to depict the biochemical degradation of myelin proteins and lipids to amino acids and fatty acids, respectively (Blümcke & Niedorf, 1966;Fernandez-Valle, Bunge, & Bunge, 1995;Gomez-Sanchez et al, 2015;Holtzman & Novikoff, 1965;Johnson et al, 1949). These "chunks" of compact myelin are cleared by macrophages that begin to infiltrate the site from the blood, 3-4 days after injury (Beuche & Friede, 1984;Brosius Lutz et al, 2017;Crang & Blakemore, 1986;Hirata & Kawabuchi, 2002;O'Daly & Imaeda, 1967;Stoll et al, 1989). These "chunks" of compact myelin are cleared by macrophages that begin to infiltrate the site from the blood, 3-4 days after injury (Beuche & Friede, 1984;Brosius Lutz et al, 2017;Crang & Blakemore, 1986;Hirata & Kawabuchi, 2002;O'Daly & Imaeda, 1967;Stoll et al, 1989).…”
Section: Myelin Phagocytosis Autophagy and Myelinophagy In Wallermentioning
confidence: 99%
“…P, primary ovoid type fiber; D, demyelinating type fiber (Jang et al, 2016) FIGURE 2 Myelin clearance mechanisms of Schwann cells in Wallerian degeneration. It has been recently reported that the receptor for phagocytosis, TAM receptor (Tyro3, Axl, and Mer), in the SC also plays a role in myelin phagocytosis after nerve injury (Brosius Lutz et al, 2017). The secreted myelin debris could be phagocytosed by DSC (b) and then digested by myelinophagy or by autophagy-independent manner.…”
Section: Myelin Phagocytosis Autophagy and Myelinophagy In Wallermentioning
confidence: 99%
See 1 more Smart Citation